2022
DOI: 10.1038/s42005-021-00787-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating time-dependent entropy production from non-equilibrium trajectories

Abstract: The rate of entropy production provides a useful quantitative measure of a non-equilibrium system and estimating it directly from time-series data from experiments is highly desirable. Several approaches have been considered for stationary dynamics, some of which are based on a variational characterization of the entropy production rate. However, the issue of obtaining it in the case of non-stationary dynamics remains largely unexplored. Here, we solve this open problem by demonstrating that the variational ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 76 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…53 . In addition, numerical optimization schemes have also been extended to systems driven in a time-dependent manner 57 , where it is as yet unclear how the deterministic scheme will perform.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 . In addition, numerical optimization schemes have also been extended to systems driven in a time-dependent manner 57 , where it is as yet unclear how the deterministic scheme will perform.…”
Section: Resultsmentioning
confidence: 99%
“…As it is possible to also trap such beads inside a cell with optical tweezers 74 , this too could be a very interesting system to study. Finally, in other recent work 57 , it has been demonstrated that inference schemes of this kind can also be made to work for non-stationary non-equilibrium states, further diversifying the scope of this class of techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Such considerations will be crucial for practical applications of the inference scheme to complex non-equilibrium systems such as biological systems, where anharmonic energy landscapes naturally arise [23][24][25][26]. However, for more generic representations of arbi-trary currents, such as in terms of a neural network (see [12,27]), such issues do not arise.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the last decades, several methods to determine the nonequilibrium nature of a system have been developed -for a recent review, see [50]. Many of these techniques also quantify how much the system is out of equilibrium, usually as a bound on the entropy production [88][89][90][91][92]. A popular technique is based on the verification of the fluctuation-dissipation relation, which relates correlation and response for equilibrium systems [93][94][95][96].…”
Section: Time Asymptoticsmentioning
confidence: 99%